Influence of Climate-Related Environmental Stresses on Economically Important Essential Oils of Mediterranean Salvia sp. - Karalija, Erna; Dahija, Sabina; Tarkowski, Petr; Zeljković, Sanja Ćavar (Frontiers in Plant Science, 2022)
Salvia L. is the largest genus in the family Lamiaceae, with about 1000 species and a nearly cosmopolitan distribution. Salvia species are used in both traditional and conventional medicines, and other numerous industries such as spices, perfumes, etc. The number of papers dealing with Salvia exceeds 12 000 and mostly investigates their chemical composition and bioactive properties. A smaller proportion of papers however consider environmental factors, mostly on the effects of microclimate conditions on its geographic distribution along an altitudinal or longitudinal gradient, and very few studies can be found on the effects of emerging stressors on the commercial production of sages of medicinal and economical importance. Here, we summarize available data on the essential oil composition of three economically important sages from the Mediterranean area, i.e., Salvia officinalis, Salvia officinalis subsp. lavandulifolia, and Salvia fruticosa, and the effects of climate-related environmental stressors on their chemical profiles. Environmental stress factors, such as an increase in soil salinity and aridity, and changes in annual average temperatures are going to impose a serious risk on the commercial production of sage essential oils, which are commercially produced in many European countries. This review highlights the already confirmed effects of these stressors on three selected Salvia species and consequently the importance of mitigating the effects of climate change on the commercial production of these essential oils.